Seri Animasi Pendek untuk Menjelaskan Fungsi Punawakan Kepada Generasi Muda - Novida Nur Miftakhul Arif (Lakon Jurnal Pengkajian & Penciptaan Wayang, 2022)
Wayang kulit contains many good values   that are still relevant today, including the Punakawan characters who always give positive messages that are actually intended for society. However, there has been a decline in interest, especially in the younger generation due to the effects of globalization and a lack of understanding of the Javanese language. The short animated series is a way of conveying good values of wayang, especially the Punakawan. This media is designed to take into account the characteristics of the target audience so that it can be easily enjoyed and understood. This research and design uses the Multimedia Development Life Cycle (MDLC) method which is elaborated with the animation design method. The data obtained comes from books and research on Punakawan, as well as the results of discussions with practitioners such as senior puppeteers in Yogyakarta. This short animated series consists of three videos that use a modern approach by incorporating lots of pop culture elements in the visual aspect that shows Punakawan’s work. There are also several supporting media such as teaser videos or anglers and short comics as prologues. This short animated series was uploaded on the Heritage Punakawan Instagram, received a positive response and showed high enthusiasm from the public.